Konsep “Loob” Menurut Orang Filipina - Christine Carmela R. Ramos (Respons: Jurnal Etika Sosial, 2020)
The paper discussed Filipino indigenous thoughts to appreciate its culture. “Loob” encompassed Filipinos’ humanity, personality, theological perspective and daily experiences. It aspired harmony with others and nature to be in union with God. The interpersonalistic characteristic of “loob” explained the dualism in body-soul and emotional-rational of the Filipinos. The paper focused on the two dimensions of “loob”: as interior and holistic. The interior “loob” affirmed the innate goodness. “Loob” is reconstructed not only the world but itself as well. The holistic concept referred to the unified entity of the world, the non-dual outlook of the world. More, the author took note of the interplay of emerging contrasts between the views of Ayn Rand and the Filipino concept of “loob”. While the Western philosophy emphasizes modern science and technology, the Eastern thinking, however, is more concerned on the inner and personal nature of the self. The Western thinking is departmentalized and detached. On the other hand, the Eastern thinking views the world of senses as ephemeral and illusory. Likewise, the Eastern thinker is acquainted through one’s personal experience and intuitive grasp of reality which is of higher value than analytical speculation